Initial Experience Assessing the Feasibility of Conscious Sedation in Patients Undergoing Transcatheter Pulmonic Valve Implantation. Issue 3 (4th May 2021) - Anchan, Rajeev; Weibeler, Diane; Venturini, Joseph M.; Dia, AbdulRahman; Gruenstein, Daniel H.; Shahul, Sajid S.; Kalathiya, Rohan; Blair, John; Paul, Jonathan D.; Nathan, Sandeep; Friant, Janet; Besser, Stephanie A.; et al.
ABSTRACT: Background : Transcatheter pulmonic valve implantation (TPVI) is a minimally invasive procedure that treats patients with dysfunction of the pulmonic valve or right-ventricular-to-pulmonary artery conduit. TPVI procedures have traditionally been performed under general anesthesia (GA), yet conscious sedation (CS) has emerged as an alternative to GA. This study assessed the feasibility of CS-TPVI compared to GA-TPVI. Methods : We performed a retrospective review of 19 consecutive patients undergoing TPVI with CS or GA. The primary endpoint was procedure success, defined as a residual gradient <20 mmHg and freedom from reoperation within 30 days. Secondary endpoints included the procedure step durations, 30-day readmission rate, composite of 90-day rehospitalization and mortality rates, procedural characteristics, and periprocedural complications. Results : Nineteen patients underwent TPVI (CS-TPVI = 8). The procedural success rate was not statistically different between cohorts; only one case in the GA-TPVI group had an elevated transvalvular gradient. The CS-TPVI 90-day composite of rehospitalization and mortality rates was not different from that of GA-TPVI. Median in-room procedure duration was less with CS (131.5 minutes, [90–173, IQR] versus 196 minutes [165–260, IQR], p = 0.007), fewer patients required vasopressors, and no patients converted from CS to GA. Contrast use, radiation exposure, length of stay, and periprocedural complications were not different between groups. Conclusions : This small, nonrandomized study reports no differences in clinical outcomes between CS-TPVI and GA-TPVI with shorter in-room duration and less vasopressor use in the CS-TPVI group. This study highlights the importance of a multidisciplinary approach in complex congenital heart disease patients and underscores the need for larger studies investigating CS-TPVI. Abbreviations: CHD: congenital heart disease; CS: conscious sedation; GA: general anesthesia; IQR: interquartile range; PA: pulmonary artery; RV: right ventricle; RVOT: right ventricular outflow tract; TAVI: transcatheter aortic valve implantation; TPVI: transcatheter pulmonic valve implantation